2010
DOI: 10.5216/cab.v11i2.1364
|View full text |Cite
|
Sign up to set email alerts
|

PARÂMETROS BIOQUÍMICOS DE Piaractus mesopotamicus E Colossoma macropomum (CHARACIDAE) E HÍBRIDO TAMBACU (P. mesopotamicus x C. macropomum)

Abstract: A study for investigating the values of plasma glucose, serum total protein and serum ions (calcium, potassium, magnesium, sodium and chloride) was carried out in young Colossomoma macropomum Cuvier, 1818, Piaractus mesopotamicus Holmberg, 1887 and the hybrid tambacu (P. mesopotamicus x C. macropomum), kept in intensive system. Glucose concentrations were higher in tambacu than in P. mesopotamicus and C. macropomum. Total protein levels were higher in P. mesopotamicus than both C. macropomum and tambacu. C. ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…These characteristics may indicate that low numbers of thrombocytes are caused by diseases, parasites, or other environmental conditions imposed on the organism. There was also lymphocytosis, eosinocytosis and monocytosis among tambaqui from excavated ponds in Iranduba and Novo Airão, unlike other studies conducted with tambaqui C. macropomum that did not observe changes in the values of leukocyte types [16][17][18][19].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…These characteristics may indicate that low numbers of thrombocytes are caused by diseases, parasites, or other environmental conditions imposed on the organism. There was also lymphocytosis, eosinocytosis and monocytosis among tambaqui from excavated ponds in Iranduba and Novo Airão, unlike other studies conducted with tambaqui C. macropomum that did not observe changes in the values of leukocyte types [16][17][18][19].…”
Section: Discussionmentioning
confidence: 75%
“…Higher glucose values were found in Manaus fish and lower in Iranduba and Novo Airão (Table 4). However, the tambaqui from Manaus may be overfed and in the process of accumulating energy 69.0 ± 1.0 a 60.9 ± 4.0 b 66.6 ± 1.5 a 54.0 ± 4.9 c 59.3 ± 3.1 c Total ammonia (mg.L -1 ) 0.01 ± 0.00 a 0.01 ± 0.01 a 0.50 ± 0.30 b 0.02 ± 0.01 a 0.60 ± 0.10 b Nitrite (mg.L -1 ) 0.00 ± 0.00 a 0.00 ± 0.00 a 0.02 ± 0.01 b 0.00 ± 0.00 a 0.01 ± 0.00 b in the form of glucose; on the other hand, the fish from Iranduba and Novo Airão may be malnourished and in physiological difficulty within the ponds [20][21][22][23] reiterate that the main difficulty for fish producers in Amazonas is acquiring feed, given the farming systems' high prices and logistical challenges. The lipid compounds (cholesterol and triglycerides) investigated reinforce low levels in the blood of fish from Iranduba and Novo Airão, such as total proteins and glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies reported the parameters of this species related to its red blood cells under the influence of exposure to nitrite (Moraes et al, 2006). The biochemical parameters of its blood, including quantification of total serum protein (Tavares-Dias and Moraes, 2010), were also previously assessed, along with the characterization of the acute inflammatory response in this species based on the counts of defensive (i.e. immunity-related) blood cells in inflammatory exudate (Martins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Blood is a liquid tissue distributed to the organs by the circulatory system and transports nutrients, hormones, electrolytes, water, residues from cellular metabolism and several other substances (VERRASTRO et al 1998). The study of blood parameters have been used as an important tool for monitoring the health status of elasmobranch (WALSH;LUER, 2004;STOSKOPF, 2010) and teleost fish MORAES, 2010).…”
Section: Introductionmentioning
confidence: 99%